Licensing of Structural Pesticide Applicators in Florida - O. Norman Nesheim; Frederick M. Fishel (EDIS, 2010)
Revised! PI-10, a 6-page fact sheet by O. Norman Nesheim and Frederick M. Fishel, explains the licensing and regulation of persons who apply pesticides to structures in Florida. Published by the UF Department of Agronomy, March 2010.